Socio-Cultural Support For The Sustainability Of Food Production And Consumption In Highland Communities In Sinjai District, South Sulawesi Province. - Ahmad, Ahfandi; Ali, Muhammad Saleh S.; Rahmadanih, Rahmadanih; Teddu, Sulaiman (Hasanuddin University, 2023)
Socio-culture is increasingly recognized as an important part towards sustainable food production and consumption.Â This evolution is reflected in the fact that socio-culture is now generally referred to as one of the main drivers of sustainable food production and consumption. This study focuses on socio-cultural aspects in relation to the food production subsystem and food consumption subsystem in highland communities in West Sinjai District, Sinjai Regency, South Sulawesi Province. Using a qualitative approach, case study method, with data collection techniques, in-depth interviews, full observation, documentation and triangulation. So that it can see in depth the socio-cultural reality of the highland community. The socio-cultural apparatus is one of the supporting factors in the realization of the sustainability of food production and consumption in highland communities. The socio-cultural apparatus is one of the supporting factors in realizing the sustainability of food production and consumption in upland communities.Â The socio-cultural component in the food production of highland communities strongly emphasizes the value of togetherness, the value of mutual cooperation and religious values. These values are implemented into food production activities from land preparation to harvesting such as;